Anti-Metabolic Syndrome Effects of Fucoidan from Fucus vesiculosus via Reactive Oxygen Species-Mediated Regulation of JNK, Akt, and AMPK Signaling - Wang, Xueliang (Molecules, 2019)
Recent studies have reported that dietary fiber improved metabolic syndrome (MetS). However, the effects of fucoidans on MetS were still not clear. In this study, we evaluated the activity of fucoidan from Fucus vesiculosus (FvF) on attenuating MetS and first elucidated the underlying mechanism. In vitro, FvF treatment remarkably lowered the level of reactive oxygen species (ROS) compared with the sodium palmitate (PA)-induced insulin resistance (IR) group. The phosphorylation level of c-Jun N-terminal kinase (JNK) was significantly decreased, while phosphorylation of protein kinase B (pAkt) level increased, compared with that of the HepG2 cells treated with PA. Thus, FvF increased glucose consumption and relieved IR via ROS-mediated JNK and Akt signaling pathways. In addition, these changes were accompanied by the activation of adenosine 5′-monophosphate-ativated protein kinase (AMPK) and its downstream targets (e.g., HMG-CoA reductase (HMGCR), acetyl-CoA carboxylase (ACC), and sterol-regulatory element-binding protein-1c (SREBP-1C)), which improved lipid metabolism in IR HepG2 cells. In vivo, FvF improved hyperglycemia and decreased serum insulin level in mice with MetS. Furthermore, we evaluated the inhibition of glucose transport by in vitro (Caco-2 monolayer model), semi-in vivo (everted gut sac model) and oral glucose tolerance test (OGTT), which indicated that FvF could significantly reduce the absorption of glucose into the blood stream, thus it could improve blood-glucose levels and IR in mice with MetS. Moreover, FvF decreased serum triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) levels and liver lipid accumulation, while increased the serum high density lipoprotein cholesterol (HDL-C) level in mice with MetS. Therefore, FvF could be considered as a potential candidate for the treatment of MetS by alleviating IR, inhibiting glucose transportation, and regulating lipid metabolism.